Potencial evocado auditivo de tronco encefálico em equinos - Gama, Juliana Almeida Nogueira da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Hearing is one of the main points of the communication process with the environment both humans and animals. The Auditory brainstem response (BAEP Brainstem Auditory-Evoked Potential) is a method that has been used in humans, dogs, cats, cattle and horses in order to identify possible hearing impairment that can’t be diagnosed during physical examination . The BAEP evaluates the integrity of the auditory pathway from the cochlea to the brainstem and allows the identification of animals with sensorineural and conductive deafness. Despite the importance of BAEP, no study to standardize its use in horses in Brazil was found. Thus, the objective of this study was to standardize the methodology for obtaining records to verify the wave latencies obtained in the examination for this species. 21 adult horses, males and females were used without previous history of hearing disorders. To perform the test, the animals were sedated with detomidine hydrochloride. Latencies of waves I, II, III, IV and V, as well as the intervals I-III, III-V and IV were identified. The mean latencies of the waves were, I wave 2.4 ms; wave II 2.74 ms ; wave III 3.61 ms; wave IV 4.61 ms and wave V 5.49 ms. The mean latencies of interpeaks were I-III 1.37; III-V 1.88 and I-V 3.26. The description of the methodology used and the availability of records and latencies can serve as a reference for studies in this species

A audição é um dos principais pontos do processo de comunicação com o meio ambiente tanto de seres humanos quanto de animais. O potencial evocado auditivo de tronco encefálico (BAEP-Brainstem Auditory Evoked Potential) é um método que tem sido utilizado em seres humanos, cães, gatos, bovinos e equinos com a finalidade de identificar possíveis alterações auditivas que não podem ser diagnosticadas durante o exame físico. O BAEP avalia a integridade das vias auditivas, desde a cóclea até o tronco encefálico e permite a identificação de animais com surdez neurossensorial e condutiva. Apesar da importância do BAEP, não foi encontrado nenhum estudo de padronização do seu uso em equinos no Brasil. Dessa maneira, o objetivo deste trabalho foi padronizar a metodologia para obtenção de registros que permitam verificar a latência das ondas obtidas no exame para essa espécie. Foram utilizados 21 equinos adultos, machos e fêmeas, sem histórico prévio de alterações auditivas. Para realização do teste, os animais foram sedados com cloridrato de detomidina. Foram identificadas as latências das ondas I, II, III, IV e V, bem como dos intervalos I-III, III-V e I-V. As médias das latências das ondas foram, onda I 2,4 ms; onda II 2,74 ms; onda III 3,61 ms; onda IV 4,61 ms e onda V 5,49 ms . As médias das latências dos interpicos foram I-III 1,37 ms; III-V 1,88 ms e I-V 3,26 ms. A descrição da metodologia utilizada e a disponibilização dos registros e das latências obtidas podem servir de referência para estudos realizados nessa espécie
Brainstem auditory evoked potential in equine
Keywords: Potenciais auditivos evocados; Tronco encefalico; Surdez; Disturbios da audição - Testes; Auditory evoked response